Efforts in Pressing the Emergence of Terrorist Network - Suka Arjawa, GPB.; Rwa Jayantiari, IGA. Mas (Udayana Journal of Social Sciences and Humanities, 2017)
This research aimed to make description on alternative way to press terrorism in Indonesia. Some approaches are adopted, especially by the government, to eliminate the terrorists, namely: a firm approach by attacking the terrorists, legal remedy by bringing them before the court and giving punishment. However, such efforts still not able to maximally pressing the terrorism. Terror in Jalan Thamrin Jakarta in the early 2016 showed that terrorism still cannot be pressed. This research aimed to give additional approaches in combating terrorism by using local wisdom. Bali as one of tourist destination in Indonesia, had twice experiences of terrorist attack with many casualties. Bali has a lot of local wisdoms which meanings can be explored. Some of it are menyama braya, mesegeh ritual, okokan arts performance and Tat Twam Asi. Therefore, there are several methods and steps which can be used to press the terrorism by exploring the meanings contained in such local wisdoms. All of that local wisdoms contains the meanings of cooperation, alertness and togetherness. The terrorists are expected to stop their terrorism attack by implementing such local wisdoms.